FORMATION AND DESCRIPTION OF THE WOMEN RIGHTS IN ISLAM (American Journal of Research in Humanities and Social Sciences, 2023)
The article deals with the issue of equality of women and men in the Islamic religion. The role of a woman in marriage, family responsibilities, relations between husband and wife, established rights and obligations regarding marriage and love are also analyzed.